Frequency, characteristics and impact of multiple consecutive nosocomial infections in patients with decompensated liver cirrhosis and ascites. Issue 5 (June 2020) - Schultalbers, Marie; Tergast, Tammo L; Simon, Nicolas; Kabbani, Abdul-Rahman; Kimmann, Markus; zu Siederdissen, Christoph Höner; Gerbel, Svetlana; Manns, Michael P; Cornberg, Markus; Maasoumy, Benjamin
Background: Nosocomial infections are a particular threat for patients with liver cirrhosis. It is not uncommon that individuals develop even several consecutive infections during a single hospital stay. We aimed to investigate the impact and characteristics of multiple, consecutive nosocomial infections. Methods: A total of 514 consecutive patients with liver cirrhosis and ascites were included and followed up for 28 days for nosocomial infection, death or liver transplantation (LTx). Laboratory values were assessed at the time of hospitalization as well as at the onset of each new infectious episode. Results: 58% ( n = 298) of the patients developed at least one nosocomial infection and in 23% ( n = 119) even multiple infections were documented during a single hospital stay. Consecutive infections usually occurred shortly after the previous episode. Spontaneous bacterial peritonitis (SBP) was the most common infection. However, the proportion of SBP declined from 43% at the first to only 31% at the third nosocomial infection ( p = 0.096). In contrast, the likelihood for other, less common types of infection such as blood stream infections increased. Third nosocomial infections were also more likely to be linked to the detection of fungal pathogens (21% vs. 52%; p = 0.001). Each additional infectious episode had a dramatic detrimental impact on LTx-free survival that was independent from the stage of liver disease (adjusted-HR: 6.76, p = 0.002 for first nosocomial infection; adjusted-HR: 14.69, p <0.001 for second nosocomial infection; adjusted-HR: 24.95, p <0.001 for third nosocomial infection). Conclusion: In patients with decompensated liver cirrhosis LTx-free survival significantly decreases with every consecutive infectious episode. Development of prevention strategies is urgently required.